Research Progress of Biodegradable Polymers in Repairing Achilles Tendon Injury - Zhang, Jinchi; Wang, Wange; Zhang, Xinan; Yang, Liqun; Zhang, JinChao (Frontiers in Materials, 2022)
Achilles tendon injury has become a common sports injury clinically, and its treatment and rehabilitation are essential, while the regenerative capacity of the Achilles tendon in adult mammals is limited. Therefore, it is necessary to promote the repair and remodelling of the Achilles tendon through efficient interventions. Biodegradable polymer materials are one of the most popular in the treatment and repair of soft tissues, ligaments, muscles, and organs injured by organisms to enhance the function of their wounded sites. Thus, it plays a specific role in “compensation” and is widely used in clinical medicine and rehabilitation. This review summarized the progress of poly (ε-caprolactone), polylactic acid, poly (lactic-co-glycolic acid), poly (trimethylene carbonate) (PTMC), and polydioxanone (PDS) in repairing Achilles tendon injury, indicating that the biodegradable polymers have succeeded in improving and treating Achilles tendon injuries. However, some problems such as lack of good affinity with cells and uncontrollable degradation of the biodegradable polymers should be overcome in repairing Achilles tendon injury. Therefore, the development of modified biodegradable polymers to make them an ideal repair material that meets the requirements is vital in improving Achilles tendon injuries. With the continuous development and close cooperation of life sciences and material sciences, excellent materials for repairing Achilles tendon injuries will undoubtedly be produced. The treatment of Achilles tendon injuries will be more straightforward, which will be a boon for many athletes.